Multimodal visual-somatosensory integration in saccade generation. - Amlôt, R; Walker, R; Driver, J; Spence, C (2003)
Neurophysiological studies have demonstrated multisensory interaction effects in the neural structures involved in saccade generation when visual, auditory or somatosensory stimuli are presented bimodally. Visual-auditory interaction effects have been demonstrated in numerous behavioural studies of saccades but little is known about interaction effects involving somatosensory stimuli. The present study examined visual-somatosensory interaction effects on saccade generation using a multisensory paradigm, whereby task-irrelevant distractors appeared spatially-coincident with, or remote from the designated saccade target. Somatosensory distractors reduced the latency of saccades when presented before the visual target and the greatest facilitation effect was observed with spatially-coincident stimuli. Visual distractors spatially-coincident with a somatosensory target reduced latency (and increased peak velocity) when presented before and after the target. Visual distractors contralateral to somatosensory targets increased saccade latency and produced high error rates of saccades made to the distractor. The high error rates and latency modulation with visual distractors is consistent with a bias for visual stimuli in the saccadic system. In the visual target condition, saccade latency was modulated by a somatosensory distractor that was entirely task-irrelevant and this effect was always greatest with spatially-coincident distractors. The multisensory distractor effects are discussed in terms of saccades being programmed to the non-target modality, the early triggering of a non-spatial saccade 'when' signal, and multisensory neuronal enhancement effects.